Komparasi model pembelajaran Problem Based Learning dan Case Based Learning terhadap kemampuan berpikir kreatif peserta didik pada mata pelajaran IPAS - Desiyamti Munawaroh; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2026)
This research aims to investigate differences in creative thinking abilities among students in the fifth grade when employing problem based learning versus case based learning in science education. A quantitative research approach was utilized in this study with a quasi-experimental design. The sample consisted of 23 students from class VA and 20 students from Class VB at SD N 1 Delanggu. Data were obtained through pre-test and post-tests administered before and after the learning interventions. Data analysis was conducted using t-tests. Findings revealed no significant difference between the two instructional approaches (sig = 0.095 > sig 0.05). Consequently, both approaches demonstrate comparable effectiveness in fostering creative thinking skills. This study indicates that educators may employ either PBL or CBL, provided adjustments are made to suit student characteristics and learning objectives. This research may also serve as a reference for other scholars in related fields.